Impact of point-of-care screening for hypertension, diabetes and progression of chronic kidney disease in rural Manitoba Indigenous communities - Harasemiw, Oksana (CMAJ, 2021)
BACKGROUND: In 2013–2015, we conducted point-of-care screening for hypertension, diabetes and chronic kidney disease in rural and remote Indigenous communities in Manitoba, Canada. In this study, we aimed to determine whether optimal follow-up care was provided, defined as proportion of individuals with appropriate kidney disease laboratory testing, medication prescriptions and physician visits. METHODS: We linked screening data from participants to provincial administrative data sets to evaluate whether frequencies of laboratory testing, prescriptions of disease-modifying medications, and primary care and nephrology visits differed in the 18 months before and after screening. We also conducted a propensity score matching analysis to compare outcomes between screened and unscreened adults. RESULTS: Of 1353 adults who received the screening intervention and who had complete administrative data available, 44% were at risk of kidney failure at screening. Among these individuals, frequencies of comprehensive laboratory testing (estimated glomerular filtration rate and urine albumin to creatinine ratio) improved by 17.0% (95% confidence interval [CI] 11.5 to 22.5), anti-hyperglycemic medications improved by 4.4% (95% CI 1.0 to 7.8), and nephrology visits for participants meeting referral criteria improved by 5.9% (95% CI 3.4 to 8.5). We observed significant improvements in laboratory testing, antihyperglycemic medications and nephrology visits in the screened group compared with the 1:1 matched comparison group. INTERPRETATION: Point-of-care screening programs in rural and remote Indigenous communities are adaptable methods for increasing awareness, monitoring risk and treating chronic diseases. Interventions such as the development of a national screening program could improve chronic disease care in high-risk populations.